Teachers’ perceptions of their self-regulated learning practices in elementary school classrooms - Greenquist-Marlett, Stephanie; Bol, Linda; Hill, Courtney (Frontiers in Education, 2025)
Self-regulated learning (SRL) is associated with adaptable, critical, lifelong thinking skills. Teachers are essential to promoting SRL in learners, yet infrequently teach these learning strategies in classrooms. We addressed three research questions: (1) How do K–5 teachers implement SRL in their teaching?, (2) How is the use of SRL strategies linked to their self-efficacy or confidence in teaching?, and (3) How do teachers differ in their use of SRL depending on school type (public vs. private)? Semi-structured interviews were conducted with 12 primary in-service teachers, sampled equally from one public and one private school, to explore their SRL practices. They frequently utilized SRL in implicit ways. Further themes included setting goals based on student needs, monitoring student progress, and thereby adapting instruction. Teachers were largely confident about incorporating SRL into their instruction. Public school participants relied on time management and tracked student progress in more summative ways than their private school counterparts.